The antimicrobial efficacy of nanographene oxide and double antibiotic paste per se and in combination: part II - Fateme Eskandari; Yasamin Ghahramani; Abbas Abbaszadegan; Ahmad Gholami (BMC, 2023)
Abstract Background Finding strategies to overcome the rising trends of antimicrobial resistance against currently available antimicrobial agents has become increasingly relevant. Graphene oxide has recently emerged as a promising material due to its outstanding physicochemical and biological properties. This study aimed to validate previous data on the antibacterial activity of nanographene oxide (nGO), double antibiotic paste (DAP), and their combination (nGO-DAP). Methods The antibacterial evaluation was performed against a wide range of microbial pathogens. Synthesis of nGO was achieved using a modified Hummers' method, and loading it with ciprofloxacin and metronidazole resulted in nGO-DAP. The microdilution method was utilized to assess the antimicrobial efficacy of nGO, DAP, and nGO-DAP against two gram-positive bacteria (S. aureus and E. faecalis), two gram-negative bacteria (E. coli, and S. typhi), and an opportunistic pathogenic yeast (C. albicans). Statistical analysis was conducted using one-sample t-test and one-way ANOVA (α = 0.05). Results All three antimicrobial agents significantly increased the killing percent of microbial pathogens compared to the control group (P < 0.05). Furthermore, the synthesized nGO-DAP exhibited higher antimicrobial activity than nGO and DAP per se. Conclusion The novel synthesized nGO-DAP can be used as an effective antimicrobial nanomaterial for use in dental, biomedical, and pharmaceutical fields against a range of microbial pathogens, including gram-negative and gram-positive bacteria, as well as yeasts.